The effect of giving moringa tempeh flour on hemoglobin levels and body weight of Wistar Rats - Cucuk Suprihartini; Arya Ulilalbab; Frenky Arif Budiman (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: Tempeh is a fermented product that has earned the nickname